Chapter Il Boccaccio di Baldassar Castiglione: la duplice immagine del Certaldese nelle pagine del Cortegiano - Palma, Flavia (Studi e saggi, 2020)
Giovanni Boccaccio is quoted several times in Castiglione's Cortegiano, but all these mentions are inserted in two specific contexts: on the one hand, the debate on literary language, developed in the letter of dedication to don Michel De Silva and in the first book; on the other hand, the definition of the joke in book II. Starting from these premises, this essay analyses the meanings of Boccaccio's presence in the Cortegiano. It shows that Castiglione's treatise provides two different and concurrent representations of the author of the Decameron: a positive one, connected to the 'questione della lingua', that offers Boccaccio as a promoter of the usage ('uso'); a critical one, deriving from the theory of the 'facezia', that makes Boccaccio a challenging and challenged model.